REVOLUTIONARY AND POST-REVOLUTIONARY PROCESSES ACROSS THE POST-SOVIET EXPANSE: CAN THEY BE COMPARED? (Ukraine and Kyrgyzstan) - BORISOV, Nikolai (CENTRAL ASIA AND THE CAUCASUS, 2006)
Recently the academic and political communities have been showing great interest in the so-called Color Revolutions in the CIS. There are doubts, however, whether the revolutions in Georgia, Ukraine, and Kyrgyzstan can be placed in the same class of political phenomena and whether a comparative analysis can produce any significant results. Anyone willing to compare them should decide, first, whether these events belong to the same class, were caused by similar factors, and produced similar impacts and, second, whether they can be described as revolutions at all.I would like to discuss this in my article and compare the so-called revolutionary events, their causes, and their consequences in Ukraine and Kyrgyzstan—enough time has elapsed since the regime change in both countries to permit a more or less objective analysis To understand which factors set the so-called revolutionary processes in motion, we should first compare the two countries’ political and socioeconomic development in the Soviet Union and after its disintegration. Haunted by the fear of Ukrainian nationalism and wishing to ease the task of governing the republic, the Bolsheviks added several, predominantly Russian, regions to the Ukrainian territory proper. The Donetsk Basin, Novorossia (the Black Sea coast of Russia), and later, in 1954, the Crimea, which never belonged to Ukraine before, became part of it. Today this territory is described as Eastern, or Southeastern Ukraine.Under Soviet power, these areas lost much of their previously Russian makeup thanks to mandatory teaching of the Ukrainian language and literature at secondary schools and Ukrainian TV. Huge numbers of people from western Ukraine moved, or were forced to move to the republic’s east, etc. This, however, did not create a single Ukrainian nation; people in the east never thought of themselves as Ukrainians and continued using the Russian tongue. After moving to the east, western Ukrainians quickly blended into the predominant mass of people, started using Russian or a dialect commonly known as “surzhik,” a mixture of Russian and Ukrainian. In Soviet times, the titular nation accounted for 75 percent of the total population, but a large number of them used Russian as the native tongue and, on the whole, belonged to Russian culture, their Ukrainian affiliation being purely token. This means that the obvious split between the Western and Eastern Ukrainians (if the latter can be described as such at all) became obvious under Soviet power. Their national and linguistic affiliation was not a big problem under the common Soviet roof, but it created many stumbling blocks in the political development of independent Ukraine.